How Does the Shrimp Farmer Respond to The Threat of Climate Change? - Fatahullah; Toiba, Hery; Sujarwo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
This research investigated how shrimp farmers perceive climate change and what factors influence their decision to implement adaptation strategies. Surveys were conducted with 150 households in Tambakan, Kalianyar, Raci 1, and Raci 2. Over the past five years, information about climate change has primarily reached farmers through radio and television (54%). The majority (96.21%) perceived climate change as manifested by altered rainfall patterns, rising pond water temperatures (98.71%), declining production yields (95.41%), and an increase in shrimp pests and diseases (96.23%). The researchers classified climate change adaptation strategies into four categories and used logit regression analysis to identify factors influencing their adoption. They found that the determinants of adoption varied across these categories. Based on these findings, the study concludes that raising awareness about the impact of climate change on shrimp farming is crucial for farmers to choose suitable adaptation strategies. Additionally, strengthening institutional support through improved access to association borrowing, markets, extension services, farm group activities, and use of climate-resistant shrimp varieties can contribute to increased farm production.